Geography of meetings fictional geographies - Pont, Karina (Geografares, 2014)
What could be possible for the contemporary art in spite of what seems to remain stuck in the school maps? This is the battle proposed in this doctoral research in education, which aims to cross disciplinary boundaries through the borders mobility between education, cartography and contemporary art; pooling efforts to create vacuoles on what is already taken as ready in the school cartography, specifically in their teaching methodologies. Thus the work of Mayana Redin, Geografia de encontros (2009-2011) will be the starting point to create interventions in two graduation environments, Escola de Educação Básica Irineu Bornhausen and the Course in Geography at the University of the State of Santa Catarina, both located in Florianópolis/SC, as experimental spots with the artist`s creative processes and what seems to not move forward in the school cartography. Inspired by Carlos Drummond de Andrade, the outcomes from these meetings encourage us to reflect upon the enchantments that long ago ceased to inhabit the school and its learning space. So, artistic creation is taken as a battle, and the images produced in the interventions, as producers of other ways to inhabit the world through the invented cartographies. Keywords: educacion; art; cartography; meetings.